Corrosion inhibition studies and Solvation Analysis of Pyridine N-oxides by Polarizable Continuum Model method - krishnan, sampath (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Solvation analysis and corrosion inhibition studies has been carried out for pyridine N oxide, 3-carboxypyridine N-oxide and 2-methylpyridine N- oxide in polar and nonpolar solvents having a wide range of dielectric constants. The test set consists of water, methanol, ethanol, acetone, dichloromethane, chlorobenzene, chloroform, toulene, benzene and carbon tetrachloride. The physical properties of the systems such as free energies of solution, electrostatic interaction, dispersive energies, repulsive energies and dipole moments are discussed.Â  Quantum mechanical self consistent fields explain the properties of the compounds satisfactorily.